2008
DOI: 10.1007/s00345-008-0253-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin protects against ischemia/reperfusion injury in rat kidneys

Abstract: Based on our results, it can be concluded that curcumin protects the kidneys against I/R injury via its antioxidant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 25 publications
4
77
0
1
Order By: Relevance
“…[34][35][36] The renal protective effects of CUR have also been evaluated in several settings, including nephrectomy, diabetic nephropathy, shock-wave lithotripsy patients, in drug induced renal injury, and finally in different ischemia and reperfusion models, and these renal protective effects seem to be related to the preservation of antioxidant enzymes and the prevention of oxidative stress, as well as the inhibition of mitochondrial dysfunction and the attenuation of inflammatory response. [37][38][39] Dexmedetomidine, a highly selective and potent a2 adrenoceptor agonist, has sedative, analgesic, sympatholytic, and hemodynamic stabilizing properties and has been widely investigated in a variety of ischemia models and shown to have protective effect on brain, lung, intestine, liver, cardiac, testicular, and kidney tissues in animal models. 40 Several human studies, focusing on antioxidant properties of Dex in I/R injury, have revealed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] The renal protective effects of CUR have also been evaluated in several settings, including nephrectomy, diabetic nephropathy, shock-wave lithotripsy patients, in drug induced renal injury, and finally in different ischemia and reperfusion models, and these renal protective effects seem to be related to the preservation of antioxidant enzymes and the prevention of oxidative stress, as well as the inhibition of mitochondrial dysfunction and the attenuation of inflammatory response. [37][38][39] Dexmedetomidine, a highly selective and potent a2 adrenoceptor agonist, has sedative, analgesic, sympatholytic, and hemodynamic stabilizing properties and has been widely investigated in a variety of ischemia models and shown to have protective effect on brain, lung, intestine, liver, cardiac, testicular, and kidney tissues in animal models. 40 Several human studies, focusing on antioxidant properties of Dex in I/R injury, have revealed conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…[33] In an acetaminophen-induced renal injury model in rats, Cekmen et al [34] showed that renal tissue MDA levels were decreased with curcumin. Moreover, tissue MDA levels were also decreased with curcumin in a renal ischemia/ reperfusion model [35] and in a methotrexate-induced hepatic injury model. [6] In the present study, hepatic and renal tissue MDA levels were found to be significantly higher in the sepsis group as compared to the control group (p<0.01 and p<0.001, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Group 2 underwent laminectomy followed by SCI and received curcumin 200 mg/kg/day orally. [22][23][24] Group 3 underwent laminectomy followed by SCI and received methylprednisolone (Prednol-L, Mustafa Nevzat Ilac Sanayi Anonim Sirketi, Istanbul, Turkey) intraperitoneally at a single dose of 30 mg/kg. Following the surgical procedure, the rats were placed in a warming chamber and their body temperatures were maintained at approximately 37°C until they were completely awake.…”
Section: Methodsmentioning
confidence: 99%